Profitability and Liquidity Analysis on Stock Returns in the Company Manufacturers Listed on the Indonesia Stock Exchange - Eve Ho; Sunarto Wage (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2022)
In business activities, of course, it is necessary to analyze the condition of the company to predict future stock prices so that expectations of high returns can be achieved. When analyzing the financial statements of a company can be carried out in various ways, one of which is by calculating the desired ratios. This study aims to determine the effect of profitability and liquidity on stock returns in manufacturing company listed on the IDX. The research population is 26 companies with a sample of 11 companies where the method used is the purposive method sampling. The type of data used is secondary data and uses quantitative methods, the data will be processed using the SPSS version 26 program. The results of the t-test research prove the return on assets partially significant effect on stock returns, net profit margin partially significant effect to stock returns, the current ratio partially does not have a significant effect on stock returns and the cash ratio partially does not significant effect on stock returns. The results of the F test show simultaneously that the return on assets, net profit margin, current ratio and cash ratio have a significant effect on stock returns. In business activities, of course, it is necessary to analyze the condition of the company to predict future stock prices so that expectations of high returns can be achieved. When analyzing the financial statements of a company can be carried out in various ways, one of which is by calculating the desired ratios. This study aims to determine the effect of profitability and liquidity on stock returns in manufacturing company listed on the IDX. The research population is 26 companies with a sample of 11 companies where the method used is the purposive method sampling. The type of data used is secondary data and uses quantitative methods, the data will be processed using the SPSS version 26 program. The results of the t-test research prove the return on assets partially significant effect on stock returns, net profit margin partially significant effect to stock returns, the current ratio partially does not have a significant effect on stock returns and the cash ratio partially does not significant effect on stock returns. The results of the F test show simultaneously that the return on assets, net profit margin, current ratio and cash ratio have a significant effect on stock returns.